2021
DOI: 10.3390/su132111695
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Leadership and Sustainable Development—A Systematic Literature Review

Abstract: The main aim of this study was to clarify the current literary inconsistencies regarding the characteristics of entrepreneurial leadership and its impact on sustainability. Additionally, another aim was to establish the framework of entrepreneurial leadership and to highlight the main gaps in the entrepreneurial leadership literature. The entrepreneurial leadership literature started to develop recently as a new leadership style that is required to fulfill the current business changes in the fourth industrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…According to Leitch and Volery (2017), entrepreneurial leadership is an effective leadership styles. Pauceanu et al (2021) emphasized the contribution of entrepreneurial leadership, by enhancing organizational innovation performance and employees' creativity and, consequently, the overall sustainable performance of the organization. Literature also supports the view that transactional leadership significantly enhances organizational learning, an important organizational resource for firms' sustainability (Barney, 1991).…”
Section: Effect Of Talent Managementmentioning
confidence: 99%
“…According to Leitch and Volery (2017), entrepreneurial leadership is an effective leadership styles. Pauceanu et al (2021) emphasized the contribution of entrepreneurial leadership, by enhancing organizational innovation performance and employees' creativity and, consequently, the overall sustainable performance of the organization. Literature also supports the view that transactional leadership significantly enhances organizational learning, an important organizational resource for firms' sustainability (Barney, 1991).…”
Section: Effect Of Talent Managementmentioning
confidence: 99%
“…Corporate social capital is a category resulting from participation in a network of relationships which grants the participants access to the resources of cooperating enterprises and those jointly produced on the basis of shared norms, principles, values, and trust. Researchers' findings include the impact of positive interpersonal relationships among employees on effective knowledge management [33] and higher job performance [34], or the importance of positive leadership on employee motivation and engagement [35], as well as on the success of organizations and their sustainable performance [36,37]. Consequently, this promotes improved operational efficiency and builds competitive advantage.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Since then, a number of scholars of the entrepreneurship field have studied the impact of entrepreneurial leadership on different types of resources to investigate their specific influence on entrepreneurial endeavours in order to develop the performance of their firm. Further, Pauceanu et al (2021) indicated that the connection between RBV and entrepreneurial leadership should be more addressed by considering entrepreneurial leadership abilities among the intangible resources that help firms to accomplish a competitive advantage, and maximize the firm's performance. Therefore, this study responded to the recommendations made by previous studies in order to extend existing knowledge in terms of the connection between RBV and entrepreneurial leadership.…”
Section: Theoretical Implicationsmentioning
confidence: 99%